HEALTHCARE RESPONSE TO LASSA FEVER IN ONDO STATE, NIGERIA: A KNOWLEDGE, ATTITUDE, AND PRACTICE SURVEY - Ekwueme, Chinedu Michael; Adekunle , Tolulope Sarah (International Research Journal Diagnostics, 2024)
Lassa fever, caused by the Lassa virus (LASV) and transmitted via the multimammate rat Mastomys natalensis, poses a significant public health concern. The virus, a member of the Arenaviridae family, was first identified in Nigeria in 1969, taking its name from the town of Lassa in Borno State. These rats, as hosts of LASV, can excrete the virus in their urine for extended periods and produce numerous offspring, making them a formidable reservoir. The zoonotic nature of Lassa fever means it is primarily transmitted from animals to humans through contact with rat excreta, urine, and secretions. This mode of transmission accounts for roughly 19% of reported cases. Furthermore, human-to-human transmission, particularly through direct contact with infected bodily fluids, is a significant concern, primarily affecting caregivers and individuals in close proximity to infected individuals. Nosocomial transmission in healthcare facilities adds to the burden of this disease on the healthcare system. This abstract emphasizes the zoonotic and human-to-human transmission of Lassa fever, highlighting its dual impact on both public health and healthcare systems.